2021
DOI: 10.1093/biolre/ioab067
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin-54 injection induces a physiological luteinizing hormone surge and ovulation in mice

Abstract: Intraperitoneal injection of kisspeptin-54 induces a surge-like release of luteinizing hormone that stimulates ovulation in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…LH release was stimulated by intraperitoneal injection of kisspeptin (Owen et al, 2021), a neuropeptide that causes gonadotropin releasing hormone to be secreted from the hypothalamus, which in turn causes release of LH into the bloodstream (Stevenson et al, 2022). The rise in serum LH peaks ~1.5 hours after kisspeptin injection and is comparable in amplitude and duration to the endogenous LH surge (Owen et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LH release was stimulated by intraperitoneal injection of kisspeptin (Owen et al, 2021), a neuropeptide that causes gonadotropin releasing hormone to be secreted from the hypothalamus, which in turn causes release of LH into the bloodstream (Stevenson et al, 2022). The rise in serum LH peaks ~1.5 hours after kisspeptin injection and is comparable in amplitude and duration to the endogenous LH surge (Owen et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…However, LH-stimulated granulosa cell motility has not been investigated in intact ovarian follicles. By using mice with an HA epitope tag on the endogenous LH receptor such that its localization could be visualized [8], and by collecting ovaries for imaging at defined times after eliciting a physiological LH surge by injection of kisspeptin [36], we obtained a precise timecourse of changes in localization of mural granulosa cells expressing the LH receptor over the period leading to ovulation. We discovered that LH stimulates granulosa cells that express its receptor to extend inwards in the follicle, intercalating between other granulosa cells.…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that kisspeptin-54 induces surge-like LH release in juvenile mice. Although the duration of the LH increase is shorter than natural surges, these mice still ovulate efficiently ( Owen et al, 2021 ). Thus, both the amplitude and duration of natural LH surges are greater than actually needed to induce ovulation in mice.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that kisspeptin-54 induces surge-like LH release in juvenile mice. Although the duration of the LH increase is shorter than natural surges, these mice still ovulate efficiently (67). Thus, both the amplitude and duration of natural LH surges are greater than actually needed to induce ovulation in mice.…”
Section: Effects Of the Chicken C-tail On Gonadotropin Synthesis And Secretionmentioning
confidence: 95%